2020
DOI: 10.1186/s12951-020-00606-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sciatic nerve regeneration with dual delivery of vascular endothelial growth factor and nerve growth factor genes

Abstract: Background: Peripheral nerve injury is one common clinical disease worldwide, in which sciatic nerve is anatomically the most challenging to regenerate given its length and large cross-sectional area. For the present, autologous nerve grafting remains to be the most ideal strategy when treating with sciatic nerve injury. However, this method sacrifices healthy nerves and requires highly intensive surgery, still calling for other advanced alternatives for nerve grafting. Results:In this study, we utilized previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…We observed a 3-fold increase in VEGF secretion over the course of the second to third week after the induction of hiPSC-MPC differentiation, which contributed to axonal growth, angiogenesis and later muscle regeneration over the course of the in vivo study. [71][72][73][74][75] Overall, the vascularized hiPSC-MPC laden muscle constructs showed increased muscle regeneration, angiogenesis and maintenance of potent stem cells compared to control groups (V2 and V1). Together, these results provide a VML repair strategy based on pre-vascularized large-scale hiPSC-derived skeletal muscle implants.…”
Section: Perfusable Construct Engineeringmentioning
confidence: 87%
“…We observed a 3-fold increase in VEGF secretion over the course of the second to third week after the induction of hiPSC-MPC differentiation, which contributed to axonal growth, angiogenesis and later muscle regeneration over the course of the in vivo study. [71][72][73][74][75] Overall, the vascularized hiPSC-MPC laden muscle constructs showed increased muscle regeneration, angiogenesis and maintenance of potent stem cells compared to control groups (V2 and V1). Together, these results provide a VML repair strategy based on pre-vascularized large-scale hiPSC-derived skeletal muscle implants.…”
Section: Perfusable Construct Engineeringmentioning
confidence: 87%
“…Additionally, a study on Ginkgo biloba extract showed that it promoted axonal angiogenesis through the modulation of related genes, including Vegf, Sox18, Prom1, and IL-6 [ 71 ]. Studies have also demonstrated the participation of Vegf [ 152 , 153 ], Prom1 [ 154 ], and another subfamily gene, Sox11 in sciatic nerve regeneration [ 155 ], and the restorative role of IL-6 has also been implied in DPN and central nervous system models [ 156 , 157 ]. Muscimol prevented hyperalgesia through the modulation of PMP22 [ 91 ], a key component of the basal lamina.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of clinically effective scaffolds. This may be due to inherent nerve complexities and a need for consideration of electrical stimulation, vascularization, and exogenous biochemical molecules [ [216] , [217] , [218] , [219] ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The incorporation methods include physical embedding and surface immobilization. For example, a gene delivery system fabricated by polyethyleneimine was used to deliver plasmid DNA (pDNA) encoding vascular endothelial growth factor (VEGF), and regenerated microvessels in both peripheral nerves and gastrocnemius muscles can be seen after in vivo transfection [ 218 ]. Advanced 3D printing may also be able to print more precise scaffolds that can improve vascularization and further improve nerve graft survival and function.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%